2017
DOI: 10.1111/jfbc.12471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maceration time on phenolic compounds and antioxidant activity of the Syrah must and wine

Abstract: The main objective of this study was to evaluate the effect of the maceration time up to 30 days on the phenolic compounds, monomeric anthocyanins, color intensity, and antioxidant activity (FRAP, DPPH, and ORAC) of both must and Syrah wine produced in the São Francisco Valley, Brazil. Up to the 15th day, the maceration process promoted an increase in phenolic compounds, while the major extraction of anthocyanins occurred up to the 20th days. The results showed the concentration of total phenolic compounds sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
4
17
4
Order By: Relevance
“…The behavior of caffeic and chlorogenic acids during maceration in the 2016 harvest can be due to the reaction between caffeic, quinic, shikimic, and tartaric acids to form phenolic acid esters, such as chlorogenic acid (Kosseva et al, 2017). The concentrations of gallic, ferulic, and p-coumaric acids found in the present study were similar to those reported by Alencar et al (2018).…”
Section: Phenolic Profile Determined By Hplc-dad-fdsupporting
confidence: 92%
See 2 more Smart Citations
“…The behavior of caffeic and chlorogenic acids during maceration in the 2016 harvest can be due to the reaction between caffeic, quinic, shikimic, and tartaric acids to form phenolic acid esters, such as chlorogenic acid (Kosseva et al, 2017). The concentrations of gallic, ferulic, and p-coumaric acids found in the present study were similar to those reported by Alencar et al (2018).…”
Section: Phenolic Profile Determined By Hplc-dad-fdsupporting
confidence: 92%
“…In the present study, both compounds reached their concentration peaks around 16-20 days of maceration. Alencar et al (2018) reported that after 20 days of maceration, cv. Syrah must contained 14.5 mg/L of (-)-epicatechin and 5.6 mg/L of (+)-catechin.…”
Section: Phenolic Profile Determined By Hplc-dad-fdmentioning
confidence: 99%
See 1 more Smart Citation
“…Process of grapes such as dehydration, maceration, and pre‐fermentation could significantly affect the phenolic compound profiles of wines (Alencar et al., ; Panceri & Bordignon‐Luiz, ; Wu et al., ). However, some grape varieties, and therefore the wines, may be genetically richer in polyphenols than the others (Padilha, Camarão Telles Biasoto, Corrêa, dos Santos Lima, & Pereira, ; Poudel, Tamura, Kataoka, & Mochioka, ).…”
Section: Introductionmentioning
confidence: 99%
“…During the maceration of Syrah grape variety, transresveratrol ranged from 0.4 to 2.2 mg/L (must to must after 10 days of maceration) reaching up to 0.6 mg/L in the wine. The maximum level observed for trans-resveratrol was reached with 10 days of maceration (2.2 mg/L)(Alencar et al, 2018). The investigation conducted on grape varieties Pinot noir and Chardonnay from the province of Bourgogne consisted of maceration in fermentation during 7 days at 25 C, and fermentation of must.…”
mentioning
confidence: 99%